Lack of Reperfusion Rather Than Number of Passes Defines Futility in Stroke Thrombectomy: A Matched Case-Control Study. Issue 9 (September 2021) - Mohammaden, Mahmoud H.; Haussen, Diogo C.; Pisani, Leonardo; Al-Bayati, Alhamza R.; Bianchi, Nicolas; Liberato, Bernardo; Bhatt, Nirav; Jillella, Dinesh; Frankel, Michael R.; Nogueira, Raul G.
Abstract : Background and Purpose: There is a robust relationship between the duration of ischemia and functional outcomes after mechanical thrombectomy. Higher number of mechanical thrombectomy passes strongly correlate with lower chances of favorable outcomes. Indeed, previous studies have suggested that after multiple passes the procedure may be futile. However, using uncontrolled thresholds to define thrombectomy futility might be misleading. We aim to compare the outcome of successful reperfusion after 4 to 5 passes and ≥6 passes with those of failed reperfusion. Methods: A prospectively acquired mechanical thrombectomy database from January 2012 to October 2019 was reviewed. Patients were included if they had intracranial internal carotid artery or middle cerebral artery-M1/M2 occlusions and either achieved successful reperfusion after ≥4 passes or failed reperfusion. Reperfused patients (mTICI2b-3) were divided into 2 subgroups; (1) 4 to 5 passes and (2) ≥6 passes. Each subgroup was compared with a matched group of mechanical thrombectomy failure (mTICI0-2a). The primary outcome was the shift in the degree of disability at 90-day as measured by the modified Rankin Scale. Results: A total of 273 patients were included. As compared with matched failed reperfusion patients (n=62), those reperfused after 4 to 5 passes (n=62) had a favorable shift in the overall modified Rankin Scale score distribution (adjusted odds ratio, 3.992 [95% CI, 1.807–8.512], P =0.001] and higher rates of functional independence (31% versus 8.9%, P =0.004, adjusted odds ratio; 9.860 [95% CI, 2.323–41.845], P =0.002) at 90 days. Similarly, when compared with a matched group of failed reperfusion (n=42), patients reperfused after ≥6 passes (n=42) demonstrated a favorable shift in the overall modified Rankin Scale score distribution (adjusted odds ratio, 2.640 [95% CI, 1.073–6.686], P =0.037) and had higher rates of functional independence (36.8% vs 11.1%, P =0.004, adjusted odds ratio, 5.392 [95% CI, 1.185–24.530], P =0.029) at 90 day. Rates of parenchymal hematoma type-2 and 90-day mortality were comparable in the reperfused and nonreperfused groups. Conclusions: Achieving reperfusion despite multiple passes leads to improved outcomes compared with failed procedures. Arbitrary uncontrolled thresholds for a maximum number of passes to predict futile recanalization may lead to inappropriate early termination of procedures. Abstract : Supplemental Digital Content is available in the text.